2020
DOI: 10.1080/12298093.2020.1727401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity and Population Structure of Wild Strains and Cultivars Using Genomic SSR Markers inLentinula edodes

Abstract: In this study, the genetic diversity and the population structure of 77 wild strains and 23 cultivars of Lentinula edodes from Korea were analyzed using 20 genomic SSRs, and their genetic relationship was investigated. The tested strains of L. edodes were divided into three subgroups consisting of only wild strains, mainly wild strains and several cultivars, and mainly cultivars and several wild strains by distance-based analysis. Using model-based analysis, L. edodes strains were divided into two subpopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Several studies have reported that the relationship between phylogenetic analysis and geographical distribution of the mushroom strains is not high. In the study of An et al analyzed to 26 A. bisporus strains using 170 genomic SSR markers, the stains were not geographical clustered [32] and L. edodes wild strains in Korea were not clustered by collected regions [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have reported that the relationship between phylogenetic analysis and geographical distribution of the mushroom strains is not high. In the study of An et al analyzed to 26 A. bisporus strains using 170 genomic SSR markers, the stains were not geographical clustered [32] and L. edodes wild strains in Korea were not clustered by collected regions [22].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies investigated the genetic diversity and population structures of several edible mushrooms, including L. edodes [20][21][22], Flammulina velutipes [23][24][25], and Auricularia auricula-judae [26]. In A. bisporus, previous studies assessed genetic diversity and population structure using RFLP markers [27], RAPD markers [28,29], SSR markers [30][31][32], and Inter Simple Sequence Repeat (ISSR) markers [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…However, it might not be the sole factor responsible for the prevalence of specific alleles in cultivars. Studies on wild and cultivated strains in Korea and China showed that the genetic diversity of cultivars is higher than that of wild strains in each country [ 27 , 28 ]. These data indicate that stable cultivars was developed by mating strains from different countries, and thus genetically distant, had been repeatably used for developing new varieties.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the moderate genetic diversity level of wild P. microspora isolates collected from across Japan ( H e = 0.56) was equivalent to or lower than wild strains of other wood-decay mushroom species. For example, H e = 0.57 in Flammulina velutipes ( Liu, Feng, Li, Yan, & Yang, 2016 ); H e = 0.52 in Pleurotus ostreatus ( Li, Liu, Zhao, & Yang, 2019 ); and H e = 0.73 in L. edodes ( Lee, Moon, Ro, Chung, & Ryu, 2020 ). In this study, compared to these wild mushrooms, the sawdust-cultivated P. microspora strains in Japan were less genetically diverse ( H e = 0.16).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, compared to these wild mushrooms, the sawdust-cultivated P. microspora strains in Japan were less genetically diverse ( H e = 0.16). Studies have also shown that the cultivars of the other mushroom species all had multiple domestication origins, i.e., H e = 0.36 in F. velutipes ( Liu et al, 2016 ); H e = 0.50 in P. ostreatus ( Li et al, 2019 ); and H e = 0.76 in L. edodes ( Lee et al, 2020 ). Thus, we propose that the natural populations of P. microspora can serve as a new genetic resource to develop effective strains for sawdust cultivation.…”
Section: Discussionmentioning
confidence: 99%